2006
DOI: 10.1007/s11121-005-0018-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Substance Use Among Young Asian Pacific Islander Men Who Have Sex with Men

Abstract: We examined patterns of substance use among young Asian Pacific Islander (API) men who have sex with men (MSM). Participants (N = 496) were recruited from sampled venues and were interviewed on substance use, sexual behaviors, and attendance at MSM social venues. Substance use prevalence was highest for alcohol (94% lifetime, 89% past 6 months), marijuana (61% lifetime, 44% past 6 months), and methylenedioxymethamphetamine or ecstasy (58% lifetime, 47% past 6 months). During the past 6 months, 24% used an illi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 31 publications
4
30
2
Order By: Relevance
“…Finally, in line with other published studies [14,15,35], we found that the use of alcohol and drugs by MSM before and during sex shows a clear association with unprotected sexual relation, which stresses the need to include substance use in future prevention messages.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, in line with other published studies [14,15,35], we found that the use of alcohol and drugs by MSM before and during sex shows a clear association with unprotected sexual relation, which stresses the need to include substance use in future prevention messages.…”
Section: Discussionsupporting
confidence: 91%
“…Studies in Catalonia have also shown a growing trend in reported sexual risk behaviours such as high number of sexual partners and unprotected anal intercourse (UAI) [5,13]. Among the reasons some authors give for these increases, particularly noteworthy are the use of alcohol and drugs before and during sexual intercourse [14,15] and the use of Internet to search for and meet partners [16,17]. Furthermore, psychosocial factors such as externalised and internalised homophobia and discrimination can lead to low self-esteem that can in turn lead to an increase in risk behaviours, difficulties when negotiating safe sex, and substance abuse [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…There is an extensive literature on non-injection drug use and HIV risk behavior in MSM populations elsewhere in the world. Many studies have found associations between sexual risk behavior and consumption of recreational drugs including crystal methamphetamine, ecstasy, cocaine, gamma hydroxybutyrate (GHB), and amyl nitrate (''poppers'') in a variety of social contexts (Choi et al 2005;Colfax et al 2001;Darrow et al 2005;Hirshfield et al 2004;Koblin et al 2006;Operario et al 2006;Rawstorne et al 2007;Spindler et al 2007;Stueve et al 2002). One study has described sexual risk behavior among members of drug-using sub-populations of urban South African MSM (Parry et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This is the case among Asian/Pacific Islander (API) MSM. Existing epidemiological data shows that API MSM engage in high levels of HIV-related risk behaviors including unprotected anal intercourse and substance use [3][4][5]. Yet, HIV prevalence and incidence rates have been much lower among API MSM than among MSM of other races/ethnicities, especially other racial/ethnic minority MSM [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%